Blended Learning: Bagaimana Persepsi Mahasiswa? - Annisa Tri Wahyuni; Latifa Yunisca; Rhomiy Handican (Pendidikan Matematika FKIP Universitas Mataram, 2023)
Changes in learning methods from offline (outside the network) or face-to-face and changing to online (in the network) or online have quite a big impact as it requires adaptation efforts. Things like cost which are also not small finally make the emergence of models for Blended Leaning more used. The purpose of this study was to determine student perceptions about the implementation of blended learning. This research is a quantitative survey type research. The survey method is a method by collecting data through respondents for research samples using a questionnaire as a data collection instrument. The data collection technique used was a Likert scale questionnaire because it aims to see student perceptions of Blended Leaninglearning. Students choose one of the available options according to what they experience during Blended Leaninglearning. Data analysis techniques in this study were carried out by reducing data, presenting data and drawing conclusions. The results of this study are that most students prefer direct classroom learning because they can better understand the lessons and can also receive direct guidance from the lecturer. Online learning is felt to be less effective by students because learning is difficult to understand and limited access is used when studying such as students' lack of understanding of IT and also internet networks that do not support online learning. So that the information that is obtained is not complete and the learning process does not go well so that it affects learning outcomes which of course are also less than optimal.